Karakteristik Campuran Laston Lapis Aus yang Menggunakan Agregat Limbah Beton - Yanti; Rais Rachman; Alpius (Paulus Civil Engineering Journal, 2021)
The research objective focuses on testing the characteristics of the Laston Lapis Aus mixture, the aggregate taken later to be studied is the aggregate of Concrete Waste. The method used in this study included testing the properties of coarse aggregate, fine aggregate and filler, after that the Laston Lapis Aus mixture design was carried out after that the marshall test was carried out while the marshalltest was carried out namely the conventional marshall to get the characteristic value. The results showed that the characteristics of the pavement material in the form of aggregates from Concrete Waste tested the 2018 Bina Marga General Specifications as road layers. Through Marshall testing, the characteristics of the Laston Lapis Aus mixture were abtained with asphalt levels of 5,50%, 6,00%, 6,50%, 7,00%, and 7,50%.